Durability of Thermal Renders with Lightweight and Thermal Insulating Aggregates: Regranulated Expanded Cork, Silica Aerogel and Expanded Polystyrene - André Morgado; António Soares; Inês Flores-Colen; Maria do Rosário Veiga; Maria Glória Gomes (Gels, 2021)
Following the trend of energy-efficient construction, renders with thermal insulation properties have been studied for replacing conventional renders. However, there are still few studies on the durability of these renders that may become a barrier for their implementation. In this study, the performance of lightweight renders for thermal insulation to accelerated aging cycles and freeze/thaw cycles is discussed. For this purpose, renders with regranulated expanded cork (GEC), silica aerogel (SA), and expanded polystyrene (EPS) were produced and tested for compressive strength, ultra-sound velocity, Young’s modulus, and thermal conductivity before and after accelerated aging cycles (hygrothermal, IR and freeze/thaw cycles). With this study, a comparison between the influence of different aggregates on renders is carried out in order to understand their effect on different properties of renders.